Energy saving from Axial Fans - Kannan, M. Munisamy, Ir. Dr.; Soong, Peng Soon, Ir.; Ramies, Govindasamy (The Institution of Engineers, Malaysia, 2013)
Link to publisher’s homepage at http://www.myiem.org